The impact of digital communications on tourism marketing - L. V. Tranchenko; N. V. Tereshchuk; R. I. Lopatiuk; O. M. Tranchenko (Kazimierz Wielki University, 2020)
The influence of digital communications on marketing in the field of tourism is investigated. The need to develop strategies for the formation of business communications in the field of tourism and indicators that allow to evaluate their effectiveness and risks is emphasized. Attention is paid to the feasibility in applying strategies of differentiated, differentiated and concentrated marketing. The relevant indicators were proposed to assess the economic effectiveness of business communication strategies: income multipliers, breakeviate level assessment formula, methodology for checking the stability of the performance indicator to change factors, and Hurwitz criterion. The considered formulas and strategies for the formation of business communications in tourism create the necessary basis for scientifically justified strategic planning of the travel company's relations with counterparties.